Killer Factor in Wine Yeasts and its Effect on Fermentation - Tredoux, H.G.; Tracey, R.P.; Tromp, A. (South African Journal of Enology and Viticulture, 2017)
The occurrence of killer factor amongst yeast strains in the Viti cultural and Oenological Research Institute (V 0 RI) yeast collection was studied. From a total of 96 strains, 85 were Saccharomyces cerevisiae of which 7 strains were killer, 9 neutral and 69 sensitive. These included some imported strains. On agar, no killer action was detected at wine pH. In fermentation studies using four grape cultivars, it was shown that where the killer yeast population was less than approximately 2,5% fermentation was not affected. At higher levels the killer yeast, in some instances, took over and completed fermentation, but the total fermentation time was never longer than that of the killer strain on its own. It was concluded that the use of a yeast strain should not hinge on its killer character but rather on its oenological characteristics.